The Competitive Position of the Economy of Poland (against the Backdrop of the Visegrad Group Countries and the Baltic States) - Changes and Determinants in the Post-accession Period - Edward Molendowski (Comparative Economic Research. Central and Eastern Europe, 2021)
The article presents the results of an analysis that compares changes in Poland's competitive position against the backdrop of the Visegrad Group (V4) countries and the Baltic States (BS3) in the post-accession period (2006-2017). This type of study has not been presented in detail in the available literature before. Therefore, the article may significantly contribute to bridging the gap. The study employs a comparative analysis of secondary data concerning the indices and pillars of economic competitiveness described in The Global Competitiveness Reports prepared by the World Economic Forum. An important element of the examina- tion was the endeavour to identify major determinants of those developments. The article ends with a summary of the most significant conclusions from the analysis presented. As confirmed by the examination, the countries covered differed widely regarding the improvement of their competitive positions in the post-accession period.
Keywords: E2; E6; F4; F5; 330; international economic competitiveness; international competitiveness of an economy; effects of EU membership; Baltic States; Visegrad Group countries; Visegrad countries; new EU Member States